การใช้ไคโทซานและแป้งเป็นสารเติมแต่งในการผลิตเยื่อกระดาษขึ้นรูปจากลำต้นข้าวโพด - วีรยุทธ เจริญปัญญาปราชญ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2010)
Cornstalk is one of the most abundant agricultural wastes in Thailand. It is usually plowed over or burnt down after corn harvestation. In this study, we aimed to use cornstalk as an alternative fiber source for molded pulp and to investigate the potential use of chitosan as an additive for molded pulp from cornstalk. Cornstalk was pulped by cooking with NaOH at 120 ºC for 2 hr. then formed into a test sheet with sizing agent (AKD) and wet strength agent (Polyamidoamine-epichlorohydrin) added. Starch and chitosan were also added in various amount to find the optimum dosage. The test sheets were dried under 20-bar pressure at 125 ºC. to imitate the procedure used in pulp molding. Commercial hardwood pulp was also prepared and formed into a test sheet in a similar fashion. The sheets were tested for structural, mechenical and barrier properties. We found that the cornstalk sheets gave better mechanical properties, air and oil resistance but poorer water resistance when compared with commercial hardwood sheets, while starch gave a slight increase in tear resistance and smoothness properties of cornstalk test sheets. Chitosan gave a slight increase in strength properties in test sheets which were made from both cornstalk and commercial hardwood pulp and can greatly decrease water absorption in cornstalk test sheets.